May You Never Hunger: Religious Foodways in Dianic Witchcraft - Noonan, Kerry (Ethnologies, 1998)
Dianic Witchcraft, a subgroup of the larger feminist spirituality movement, was founded in the early 1970s. Dianics practice feminist witchcraft and meet in female-only covens, focusing solely on the Goddess. I examine this emerging tradition using Deborah Heisley's theories about the perceived gendered nature of food, as well as the thinking of Susan Starr Sered about the role of food in female-dominated religions. How does a religious group composed entirely of women and consciously focused on women’s lives deal with food within religious rites and outside of them? Do the foods used by Dianic witches reflect their political or spiritual belief Systems? By analyzing the food practices at a large, Dianic community holiday ritual in Los Angeles and through interviewing two members of Dianic covens about their personal religious practices involving food, I propose some preliminary findings about the role of food in this growing spiritual tradition.